PELAKSANAAN PROGRAM JAMINAN KESEHATAN NASIONAL DI RUMAH SAKIT ANDI MAKKASAU KOTA PAREPARE - Irssyad Dhahri; HASRIANA HASRIANA (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2018)
This study aims to determine the fulfillment of the rights of patients in hospitals Andi Makkasau, differences between patient care BPJS seen from grade levels of care, difficulties in the implementation of JKN in hospitals Andi Makkasau Parepare. To achieve these objectives, the technique of collecting data through observation, questionnaires, interviews, and documentation. Data obtained from the research that was processed using descriptive and qualitative analysis to determine the extent of implementation of the program in hospitals Andi JKN Makkasau Parepare. The results showed (1) the rights of the patient, the BPJS be patient in hospitals Andi Makkasau have not been met optimally due to entitlements for patients given the different ways by the hospital either on the number of doctors and nurses in accordance with the class of member pesertaan patients BPJS. (2) there is a difference of service that is provided by the hospitals Andi Makkasau to patients class I, class II and class III. The hospitals provide fast service to patients class I, the service is sometimes slow and sometimes fast in the treatment room class II and slow service in the treatment room class III. (3) The obstacles to the implementation of JKN Hospital Andi Makkasau Parepare consists of the resistance of the patient, family members who are having difficulty communicating with the doctors and nurses, who in complaining about the families of patients in the treatment room class III, an obstacle to the Hospital in running Andi Makkasau JKN in hospitals because many patients are not clear membership status. So that the hospitals provide to the patient's policy to take care of membership in BPJS. The next obstacle is the hospitals Andi Makkasau to governments that use sound card Indonesia, where some of the patients who come to hospitals Andi Makkasau carry a card but apparently the card can not be used again. The hospitals themselves have confirmed this to the government, but the Health Department argued that there is a community beberpa KIS holder which has been revoked on the grounds the use of the card holder is not feasible to have the KIS.